한반도에서 GPS 측위를 위한 GIM과 SBAS 전리층 모델링 성능 분석 - 이형석; 박관동; Hyung-Seok Lee; Kwan-Dong Park (Journal of Positioning, Navigation, and Timing, 2025)
The performance of the Korea Augmentation Satellite System (KASS), MTSAT Satellite-Based Augmentation System (MSAS), and BeiDou Satellite Augmentation System (BDSBAS) is respectively analyzed in the Korean Peninsula and its surrounding regions. The analysis is focused on comparing ionospheric vertical delay values based on the Grid Ionospheric Vertical Error (GIVE) provided by the Satellite-Based Augmentation System (SBAS), considering regional and seasonal characteristics. The results, assuming users located in Korea, indicate that KASS provides high consistency across seasons, regions, and Ionospheric Pierce Point (IPP) inclusion rates, exhibiting excellent performance based on precise positional accuracy. MSAS shows comparable performance to KASS in low-latitude regions but displays a tendency of decreased accuracy with increasing latitude. BDSBAS provides modeling of the ionospheric vertical delay that most closely resembles the Global Ionospheric Map (GIM). However, it has the lowest IPP inclusion rate within the Korean Peninsula, indicating limited availability. Additionally, analysis of data from the DAEJ (Daejeon) and CHAN (Changchun) sites shows that ionospheric delay corrections based on GIVE provided by SBAS yield results very similar to those obtained using GIM. Notably, at the DAEJ site, SBAS outperformed GIM, and at the CHAN site, SBAS proved to be a sufficient replacement for GIM.